Odpowiedzi

  • Użytkownik Zadane
2010-01-05T22:46:00+01:00
A) x+y=2
x-y=0

y=2-x
x-2+x=0
y=2-x
2x=2 /:2
y=2-x
x=1
y=2-1
x=1
y=1
b) x+2y=9
-x-3y=16
x=9-2y
-9+2y-3y=16
-y=25
y=-25
x=9-2*(-25)
x=59
1 5 1
2010-01-05T22:47:42+01:00
1.

x=2-y
x-y=0

x=2-y
2-y-y=0

x=2-y
2y=2

y=1
x=1



2.

x=9-2y
-x-3y=16

x=9-2y
-(9-2y)-3y=16

x=9-2y
-9+2y-3y=16

x=9-2y
-y=25

y=-25
x=59
1 5 1
Najlepsza Odpowiedź!
2010-01-05T22:52:57+01:00
X+y=2
x-y=0

x = 2 - y
2 - y - y = 0

x = 2 - y
-2y = -2 I : (-2)

x = 2 - y
y = 1

x= 2 - 1
y = 1

x = 1
y = 1



x+2y=9
-x-3y=16

x = 9 - 2y
- (9 - 2y) - 3y = 16

x = 9 - 2y
-9 + 2y - 3y =16

x = 9 - 2y
-y = 16 + 9

x = 9 - 2y
-y = 25 I * (-1)

x = 9 - 2y
y = -25

x = 9 - 2 * (-25)
y = -25

x = 9 + 50
y = -25

x = 59
y = -25
1 5 1